PENGARUH KUALITAS PRODUK, HARGA, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SIRUP MARJAN - Brawijaya Siraj, Syah Ammar (Ekomania, 2024)
The food and beverage industry is an industry with quite fierce competition, where companies must implement appropriate strategies to attract consumers. Strategy formulation is necessary because many people, especially in the beverage industry, choose purchasing decisions, and syrup is a beverage product that is widely used by the community, particularly the Marjan product that has been distributed in various regions of Indonesia. This study aims to determine the influence of product quality, price, and advertising on the purchasing decisions of Marjan products. The method used in this research is quantitative research with SEM analysis techniques. The sampling technique used is non-probability sampling, with the purposive sampling method, then the data obtained is processed using SmartPLS. The results of this study indicate that product quality and price have a significant effect on the purchasing decisions of Marjan products, while advertising does not have a significant effect on the purchasing decisions of Marjan products.